Tuberous Sclerosis and Neonatal Astrocytoma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The relative value of neural imaging studies in the diagnosis of a neonatal astrocytoma associated with tuberous sclerosis is reported from the Departments of Neurosciences, Pediatrics, and Pathology, University of California, San Diego, CA.